2011
DOI: 10.1172/jci42090
|View full text |Cite
|
Sign up to set email alerts
|

Epithelium-specific deletion of TGF-β receptor type II protects mice from bleomycin-induced pulmonary fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is a chronic fibroproliferative pulmonary disorder for which there are currently no treatments. Although the etiology of IPF is unknown, dysregulated TGF-β signaling has been implicated in its pathogenesis. Recent studies also suggest a central role for abnormal epithelial repair. In this study, we sought to elucidate the function of epithelial TGF-β signaling via TGF-β receptor II (TβRII) and its contribution to fibrosis by generating mice in which TβRII was specifically in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
151
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 200 publications
(165 citation statements)
references
References 46 publications
14
151
0
Order By: Relevance
“…Overall, these results suggest a key role for Smad3 in coordinately regulating ␣-SMA gene expression through requisite interactions with ␤-catenin/CBP in TGF-␤1-induced EMT in AEC. Together with our recent demonstration that lung epithelial-specific knock-out of TGF-␤ receptor type II reduced phosphorylation of Smad3 in response to TGF-␤ and increased survival in and resistance to bleomycin-induced pulmonary fibrosis (59), our data suggest that Smad3 is a key factor in TGF-␤-mediated EMT/fibrosis.…”
Section: ␤-Catenin/cbp and Smad3 Interactions In Emtsupporting
confidence: 81%
“…Overall, these results suggest a key role for Smad3 in coordinately regulating ␣-SMA gene expression through requisite interactions with ␤-catenin/CBP in TGF-␤1-induced EMT in AEC. Together with our recent demonstration that lung epithelial-specific knock-out of TGF-␤ receptor type II reduced phosphorylation of Smad3 in response to TGF-␤ and increased survival in and resistance to bleomycin-induced pulmonary fibrosis (59), our data suggest that Smad3 is a key factor in TGF-␤-mediated EMT/fibrosis.…”
Section: ␤-Catenin/cbp and Smad3 Interactions In Emtsupporting
confidence: 81%
“…29 It has been shown that activation of TGF-b-Smad signaling induces the expression of specific miRNAs that, in turn, may modulate TGF-b-Smad signaling in a feedback manor. [30][31][32] For example, TGF-b1 induces miR-9-5p expression, while overexpression of miR-9-5p in lung fibroblasts inhibits TGFbRII expression and prevents myofibroblast differentiation, ECM deposition, and organ fibrogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…We further identified that Fstl1 regulates epithelial injury through modulating TGF-1/BMP signaling. Activation of TGF-1 (Sime et al, 1997;Munger et al, 1999;Zhao et al, 2002;Li et al, 2011) and inadequate BMP signaling (but not BMP expression; regulates TGF- and BMP signaling, leading to epithelial injury and fibroblast activation. The precise mechanisms by which FSTL1 exerts its function, if and how FSTL1 regulates epithelial apoptosis, fibroblast proliferation/migration, and myofibroblasts' prolonged survival, are actively pursued in our laboratories.…”
Section: Discussionmentioning
confidence: 99%